Ant colony optimization (ACO) algorithm for CNC route problem - Wan Nur Farhanah , Wan Zakaria (2012)
Printed Circuit Boards (PCB) have copper tracks connecting the holes where the components are placed. They are designed specially for each circuit and makes constructive very easy without any wires. The holes on the PCB had been drilled by using Computer Numerical Controlled (CNC) machines. However, the CNC machines do not choose the optimal route when completing their task and this caused the high cost problem on the machining. This project proposes a new optimization technique which applies ant behavior, for finding the optimal route in PCB holes drilling process. The amount of phenomenon on the shortest path proves that ACO-based approach is capable to optimize the route taken for CNC machine in order to drill the holes on PCB. This project is about to develop a software which applying ACO algorithm in order to calculate the shortest path available that can reduce the time taken to drill the entire hole of PCB. The GUT will be display the shortest path that should be taken by user and give user authority to manipulate the coordinate based on the requirement.